AN ANALYTICAL STUDY OF THE DIVERSITY AND VARIABILITY OF CRITICAL APPROACHES IN HAZM AL-QARTAJANNI’S “MINHAJ AL-BULAGHA WA SIRAJ AL-UDABA” - Moussaoui, Ismail (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The research aims to analyze one of the significant works in Arabic rhetoric and critical studies, Minhaj al-Bulaghā’ wa Sirāj al-Udabā’ by the Andalusian critic and poet Hazim al-Qartajanni. The study seeks to clarify and demonstrate the author's methodology in addressing linguistic, rhetorical, and critical issues, as well as his approach to analyzing and interpreting them. It highlights the integration of knowledge and methodologies through the use of induction and textual documentation as a systematic method to compile argumentative evidence. This approach underscores the uniqueness of the book's author by deconstructing its structural and semantic components and describing them to reach conclusions, analyze content, interpret it, and compare it with Arab and Greek heritage to highlight the findings. To achieve this, two research methodologies were adopted: First, the integrative approach, which emphasizes the interconnectedness of linguistic sciences and rhetorical critical issues by employing tools that study the research topic from all knowledge dimensions and eliminate barriers between specialized divisions. Second, the descriptive-analytical approach, which involves analyzing the critical issues presented in the book based on observation and research mechanisms to collect information and data from the primary source, Minhaj al-Bulaghā’ wa Sirāj al-Udabā’. The analysis aims to explain and interpret the content, draw conclusions, and provide commentary. The findings of the research reveal the diversity and complexity of critical topics addressed by al-Qartajanni. He adopts a logical perspective that integrates Greek and Arabic cultural elements in his analyses, uncovering the principles and foundations upon which rhetoric is built within the framework of a discipline supported by logic and wisdom in Arabic rhetoric.